“ Roçado vira capoeira! ”: dinâmica das práticas agrícolas de tiradores de açaí no município de Afuá – Pará - ARANHA, Heldiane Alves (Universidade Federal do Pará, 2022)
This dissertation describes and analyzes, through a case study, agricultural and extractive practices performed by riverine communities in the Queimada Island, in the municipality of Afuá, State of Pará, Brazil. The objective is to understand and highlight the articulation of riverine family farming and management of natural resources, through which they seek their physical and social reproduction as Amazonian autonomous peasant communities. We studied three family units of production, whose practices on their small agricultural fields and